2004
DOI: 10.1111/j.1468-3083.2004.00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital syphilis presenting with nephrotic syndrome and leucocytoclastic vasculitis

Abstract: Nephrotic syndrome is a well-recognized entity in congenital syphilis but leucocytoclastic vasculitis has not yet been described. We report a case of nephrotic syndrome and leucocytoclastic vasculitis associated with congenital syphilis in a 45-day-old male infant who did well after treatment with intravenous penicillin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 3 publications
(6 reference statements)
1
9
0
Order By: Relevance
“…There have been reports concerning vasculitis in acquired and congenital syphilis [18][19][20][21]. Leucocytoclastic vasculitis of post-capillary venules in papulopurpuric lesions of the dermis is reported in congenital syphilis [20]. Small vessels in the eye might also be involved and the cluster of shaped chorio-retinal atrophy in our patients also suggested segmental vasculitis in choriocapillaries, which showed a lobular pattern.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…There have been reports concerning vasculitis in acquired and congenital syphilis [18][19][20][21]. Leucocytoclastic vasculitis of post-capillary venules in papulopurpuric lesions of the dermis is reported in congenital syphilis [20]. Small vessels in the eye might also be involved and the cluster of shaped chorio-retinal atrophy in our patients also suggested segmental vasculitis in choriocapillaries, which showed a lobular pattern.…”
Section: Discussionsupporting
confidence: 58%
“…Segmental validity observed in our study might be explained by the above speculation. There have been reports concerning vasculitis in acquired and congenital syphilis [18][19][20][21]. Leucocytoclastic vasculitis of post-capillary venules in papulopurpuric lesions of the dermis is reported in congenital syphilis [20].…”
Section: Discussionmentioning
confidence: 99%
“…The primary involvement of vessels usually presents as syphilitic aortitis affecting the vasa vasorum 6 . Only a few cases of LCV associated with syphilis have been reported 7–9 . Our case suggests that leukocytoclastic vasculitis be included in the possible histologic features of primary syphilis.…”
mentioning
confidence: 63%
“…Another study in Brazil identified nephrotic syndrome in 2 (5.3%) of 38 infants that were diagnosed with congenital syphilis at birth or within the first 4 weeks of life 5) . Appropriate penicillin and supportive therapy can allow complete clinical recovery from these conditions 1,[5][6][7] .…”
Section: Discussionmentioning
confidence: 99%
“…Addi-tional symptoms such as fever, anemia, renal manifestations, and pneumonia alba can also be observed 1,2) . This paper presents a case of congenital syphilis with nephrotic syndrome and pneumonia alba in a newborn delivered by a mother that did not receive prenatal care.…”
Section: Introductionmentioning
confidence: 99%